Analyzing the Competence of Pre-Service Chemistry Teachers in Designing Psychomotor Assessment Instruments for Basic Chemistry Laboratory Practices - Munawwarah, Munawwarah; Zubair, Sakinah (IJCER (International Journal of Chemistry Education Research), 2025)
ABSTRACT: This study investigates the competence of pre-service chemistry teachers at Universitas Negeri Makassar in designing psychomotor assessment instruments for basic chemistry laboratory practices. Employing a descriptive quantitative approach, the study aimed to evaluate the alignment of these instruments with laboratory procedural guidelines and identify challenges faced by pre-service teachers. A sample of 30 students, selected through random sampling, participated in project-based tasks to develop psychomotor instruments corresponding to six basic chemistry laboratory activities. Data were collected through skill tests and questionnaires, analyzed descriptively to determine the alignment and effectiveness of the instruments. The findings reveal that most instruments demonstrated strong alignment with procedural steps, particularly in the cases of Solution Preparation and Separation Techniques, which received high scores for clarity, well-structured rubrics, and ease of implementation. However, challenges were noted in integrating explicit safety protocols and balancing the level of difficulty in instruments such as Redox Reactions and Functional Group Identification, which exhibited minor discrepancies. The study underscores the importance of aligning assessment instruments with laboratory standards and enhancing training programs to address both cognitive and psychomotor dimensions effectively.